Anxiety in second and foreign language learning among Universiti Teknologi Malaysia (UTM) students - Rafek, Mahfuzah (2010)
Many researchers have found that second and foreign language learning can sometimes be a traumatic experience for many students (Zheng, 2008). This feeling is strongly related to many sources such as language proficiency, language difficulties, anxiety-provoking situations and many more. This study is conducted to determine the anxiety level and the students’ perceptions in second and foreign language learning. Apart from that, this study is also conducted to determine the differences of anxiety level according to gender, race and the two groups; the second language learners and the foreign language learners. A total of 113 respondents were taken among the Universiti Teknologi Malaysia (UTM) students where 66 of them were chosen from English for Academic Communication (UHB 1412) classes and the remaining 47 students were taken from the foreign languages classes such as French, Japanese and Mandarin. The instrument used in this study was a set of questionnaire adapted from the measurement scale of language anxiety called the Foreign Language Class Anxiety Scale (FLCAS) designed by Horwitz (1983). This questionnaire was used to determine the anxiety level for both second and foreign language groups. The questionnaire consisted of two sections which were the personal details and statements of contributing factors of anxiety. The factors are Communication Apprehension, Fear of Negative Evaluation, General Feeling of Anxiety and Overall Level of Anxiety. The data obtained were analyzed by using SPSS version 13.0 involving percentage, frequency, t-Test and One- Way ANOVA. The findings in this study show that there are significant differences of anxiety level in gender for Communication Apprehension and Fear of Negative Evaluation factors for both the second and foreign language groups. Significant differences are also found in race for Communication Apprehension and General Feeling of Anxiety factors for foreign language group. The findings also show significant differences in both groups only for Communication Apprehension, General Feeling of Anxiety and Overall Level of Anxiety.